Pembuatan Sistem Akuisisi Gas Karbon Monoksida Berbasis ATMega8535 - Nurhikmah Nurhikmah; Iwan Sugriwan; Ade Agung Harnawan (Lambung Mangkurat University Press, 2019)
ATMega8535 microcontroller based data acquisition system for measure carbon monoxide gas with TGS 2600 carbon monoxide sensor has been realized. The equation of sensor characteristic is obtained by compared the value of carbon monoxide gases with voltage signal from TGS 2600 carbon monoxide sensor. The value of carbon monoxide gases concentration measured by Sanfix. The equation of sensor characteristic gave formula V = 0,1266 ln(x) + 0,0049, which V in voltage (volt) and x in part per million (ppm). The voltage signal as a product of sensor conditioned by voltage follower that applying OP07. the output signal from voltage follower connected with port A0, analog input in ATMega8535 microcontroller. Port A0 in ATMega8535 microcontroller has analog to digital converter (ADC) internally. The measurement data is displayed on the LCD character 16x2 and laptop via serial communication with Delphi interface program that it could noted the data in real time and could store the measurement data onto file in the form .xlsx. the system also used XAMPP program to store measurement data onto the form database. The range measurement of measuring instrument made is 6 to 80 ppm.